The effect of long term bisphosphonate therapy on trabecular bone strength and microcrack density - Jin,A; Cobb,JP; Hansen,U; Bhattacharya,R; Reinhard,C; Vo,N; Atwood,R; Li,J; Abel,RL (Bone & Joint Research, 2017)
ObjectivesBisphosphonates (BP) are the first-line treatment for preventing fragility fractures. However, concern regarding the efficacy is growing because bisphosphonate is associated with over-suppression of remodelling and accumulation of microcracks. While DEXA scanning may show a gain in bone density the impact of this class of drug on mechanical properties remains unclear. We therefore sought to quantify the mechanical strength of bone treated with BP (oral alendronate for this study), and correlate this with the microarchitecture and density of microcracks in comparison with untreated controls. MethodsTrabecular bone from hip-fracture patients treated with BP (n=10) was compared to naïve fractured (n=14) and non-fractured controls (n=6). Trabecular cores were synchrotron and micro-CT scanned for microstructural analysis including quantification of bone volume fraction, micro-architecture and microcracks, then mechanically tested in compression. ResultsBP bone was 28% lower in strength than untreated hip-fracture bone and 48% lower in strength than and non-fracture control bone (4.6 vs 6.4 vs 8.9 MPa). BP treated bone had 24% more microcracks than naïve fractured bone and 51% more than non-fractured control (8.12 vs 6.55 vs 5.25 /cm2). BP and naïve fracture bone exhibited similar trabecular microarchitecture, with significantly lower bone volume fraction and connectivity than non-fractured controls. ConclusionsBP therapy had no detectable mechanical benefit. Instead its use was associated with substantially reduced bone strength. This low strength was probably due to the greater accumulation of microcracks and a lack of any discernible improvement in bone volume or microarchitecture. This preliminary study suggests that the clinical impact of BP induced microcrack accumulation may be substantial and long term.